Etnografía visual de las prácticas estatales en el Registro Civil, años 1965-2005: interpretación sobre la base de la película "La muerte de un burócrata" - Ruano Peñafiel, Glenda Verónica (2018)
The present scientific article, reasons on the visual resources interpreted in the light of the film "The death of a bureaucrat", that show the visual ethnography, the manifestations and behaviors that approach the reality of the social meanings of the practices of the street bureaucracy and how it influences the daily rapprochement with citizens who so much need public services, reflected through the film industry as a modus of everyday life to be shown as a resource that awakens many perceptions. This study in the first instance deciphers the repetitive social meanings of the language forms of the people's apparatus of the film, analyzes the social reliefs that occurred in a real entity (Ecuadorian Civil Registry), and finally compares, reflects and corroborates, whether the modes of conduct; past and present of both corpus, can be associated and converted into organizational competencies.